2022
DOI: 10.1111/anae.15841
|View full text |Cite
|
Sign up to set email alerts
|

A model to predict difficult airway alerts after videolaryngoscopy in adults with anticipated difficult airways – the VIDIAC score

Abstract: A model to classify the difficulty of videolaryngoscopic tracheal intubation has yet to be established. The videolaryngoscopic intubation and difficult airway classification (VIDIAC) study aimed to develop one based on variables associated with difficult videolaryngoscopic tracheal intubation. We studied 374 videolaryngoscopic tracheal intubations in 320 adults scheduled for ear, nose and throat or oral and maxillofacial surgery, for whom airway management was expected to be difficult. The primary outcome was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…Patients with pharyngolaryngeal lesions are at high risk for difficult tracheal intubation [6][7][8][9][10] with an expected incidence up to 28%, 7 which is attributed to the size, location, bleeding tendency, risk of swelling, and impaired view during airway management. 6,7,28 Predictive tests, developed in cross-sectional surgical populations with a low average risk, are suspected to have poor discrimination in patients with laryngopharyngeal disease, as they are not tailored to these patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with pharyngolaryngeal lesions are at high risk for difficult tracheal intubation [6][7][8][9][10] with an expected incidence up to 28%, 7 which is attributed to the size, location, bleeding tendency, risk of swelling, and impaired view during airway management. 6,7,28 Predictive tests, developed in cross-sectional surgical populations with a low average risk, are suspected to have poor discrimination in patients with laryngopharyngeal disease, as they are not tailored to these patients.…”
Section: Discussionmentioning
confidence: 99%
“…First, the sample size should ensure an accurate estimate of the overall outcome risk. Based on literature review and our own in-house data, 6 , 7 , 9 , 22 we assumed a primary end point prevalence of 0.15 in patients undergoing otorhinolaryngologic surgery and a margin of error ≤0.05. Second, the sample size should lead to a shrinkage of predictor effects of 10%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that airway operator skill and experience affect performance of tracheal intubation [2]; therefore, skilled senior airway operators are often favoured participants in interventional studies. However, this should not be confused with the videolaryngoscopic intubation and difficult airway classification (VIDIAC) study [3], which is a prospective observational multivariable prediction model development and validation study.…”
mentioning
confidence: 99%
“…We read with great interest the study by Kohse et al. [1], who have developed a scoring system: the videolaryngoscopic intubation and difficult airway classification (VIDIAC) score and concluded that this model will be of significant help to anaesthetists in terms of airway management when planning follow‐up anaesthesia. However, we would like to raise some questions regarding the study.…”
mentioning
confidence: 99%